In Cyprus, 'midwifery is dying.'. a qualitative exploration of midwives' perceptions of their role as advocates for normal childbirth - Coxon, Kirstie; Hadjigeorgiou, Eleni (My University, 2014)
Background: advocacy has been identified as vital for improving maternal and newborn health. In many countries, midwives struggle to advocate for women; in Cyprus, there has been no research into perceptions of advocacy amongst midwives. Aim: this study provides an exploration of the perceptions of midwives as client advocates for normal childbirth in Cyprus. Design: a qualitative approach was adopted, using participant observation and semi-structured interviews with a purposive sample of twenty experienced midwives. A thematic approach was taken for the analysis. Findings: five main interconnected themes emerged, two of which, 'Lack of professional recognition' and 'Deficiencies in basic or continuing education' presented barriers to midwives' adoption of an advocacy role. Three themes reflected structural factors that also discouraged midwives from acting as advocates: these were 'physician dominance', 'medicalisation of childbirth' and 'lack of institutional support'. Conclusion: advocacy is a demanding and challenging role and midwives should be empowered to feel confident in undertaking this role through continuing professional education programmes and professional recognition. In order to be effective advocates, midwives needed to be recognised and valued by the public and by other health professionals as equal partners within the multidisciplinary team. However, midwives in Cyprus find themselves in difficult situations when advocating normal childbirth due to medical domination of the health services, medicalisation of childbirth and inadequate institutional support. Implications for practice: in this setting, midwives need to gain professional recognition, to have more effective basic and continuing education programmes and receive better support from managers and policy makers in order to become advocates for normal childbirth.
Keywords: Advocacy; Midwives; Normal birth; Perceptions